(untitled) (Analysis of International Sciences, 2023)
Due to the tightening of the regulation of electromagnetic fields in foreign standards and the integration of the regulatory legal framework of Russia into the regulatory legal structure of developed countries, the problem of human electromagnetic safety is becoming more urgent, and its social significance will increase in the future.